Analysis of Controlling Effect of Temperature–Pressure Conditions on Hydrocarbon Generation of Source Rocks - Guo, Ruichao; Zhang, Guanlong; Zeng, Zhiping; Wang, Qianjun; Zhao, Leqiang; Wang, Jianwei; Yu, Tengfei; Gao, Jianxiong (Frontiers in Earth Science, 2022)
The thermal evolution of source rocks and the generation of oil and gas were not isolated reactions of kerogen pyrolysis but were comprehensively controlled by many influencing factors. In this study, using Permian source rock samples from Junggar Basin, a large number of high-temperature thermal simulation experiments were carried out to study the characteristics of kerogen, for example, thermal evolution degree and hydrocarbon yield, and their influences under the open system, closed system, and different temperature–pressure conditions. The results show that the hydrocarbon yield under the low heating rate is higher than that under the high heating rate, and the hydrocarbon generation reaction can be fully carried out under the low heating rate, which is more favorable for hydrocarbon generation; with the increase in pressure in the reaction system, the dominant frequency of activation energy of hydrocarbon generation gradually decreases. In terms of the hydrocarbon yield, the oil yield is higher in a high-pressure environment, especially the yield of C6-14 component in hydrocarbons is obviously increased, while there is a relatively small difference between the C14+ components. The result of this research provides a scientific evidence for evaluating the evolution process, hydrocarbon generation kinetics, and hydrocarbon resource potential of source rocks under different temperature–pressure conditions.